The Influence of Capital Structure, Profitability and Firm Size on Company Value - Fadhilah, Umi Nurul; Nurcahyono, Nurcahyono (Economics and Business International Conference Proceeding, 2024)
This study aims to empirically prove the influence of capital structure, profitability and company size on the value of companies in the health sector that have been listed on the Indonesia Stock Exchange (IDX) in 2021 - 2023. The sample selection technique was carried out by the purposive sampling method obtained by 14 companies so that the number of samples used was 42 as observation data. This study uses quantitative methods and multiple linear regression analysis processed using the SPSS version 26 program to test the relationship between the variables studied. The results of this study show that capital structure (DAR) has a negative effect on the value of the company, while the capital structure (DER) has no effect on the value of the company. Profitability (ROA and ROE) has no effect on the company’s value. The size of the company has no effect on the value of the company.